Electrochemical Characterization of Battery Materials in 2‐Electrode Half‐Cell Configuration: A Balancing Act Between Simplicity and Pitfalls. Issue 8 (3rd May 2021) - Heubner, Christian; Maletti, Sebastian; Lohrberg, Oliver; Lein, Tobias; Liebmann, Tobias; Nickol, Alexander; Schneider, Michael; Michaelis, Alexander
Abstract: The development of advanced battery materials requires fundamental research studies, particularly in terms of electrochemical performance. Most investigations on novel materials for Li‐ or Na‐ion batteries are carried out in 2‐electrode half‐cells (2‐EHC) using Li‐ or Na‐metal as the negative electrode. Although such cells are easy to assemble and generally provide sufficient stability, scientists should be aware of any effects that may influence the measurements, and care should be taken when interpreting the corresponding results. The present work addresses specific effects that can affect the electrochemical response of measurements in 2‐EHC. Critical points to be considered for long‐term cycling tests and impedance analyses are discussed and illustrated with relevant examples. The different behavior of electrochemically deposited and pristine alkali metal electrodes is shown, deriving the corresponding impact on the characterization of the actual material of interest. We demonstrate possible impacts of anode‐cathode crosstalk effects on the evaluation of measurements in 2‐EHC and highlight challenges and pitfalls in the interpretation of measurements in 2‐EHC with respect to kinetic and thermodynamic properties and battery performance. These findings contribute to the understanding of the limitations of electrochemical characterization in 2‐EHCs and should be carefully considered by researchers when evaluating novel battery materials. Abstract : Beware of the half‐cell effects : Electrochemical measurements in two‐electrode half cells (2‐EHC) are a core element of modern battery research. Here, we present hardly noticed but omnipresent effects that sabotage the interpretation of 2‐EHC measurements. Recommendations for experimental design and practical implementation are given to avoid misinterpretations, improve comparability between independent research studies, enable more valid conclusions, and to identify promising research trends.